Evaluation of root canal morphology in permanent maxillary and mandibular anterior teeth in Saudi subpopulation using two classification systems: a CBCT study - Azhar Iqbal; Mohmed Isaqali Karobari; Mohammad Khursheed Alam; Osama Khattak; Sultan Metab Alshammari; Abdul Habeeb Adil; Tahir Yusuf Noorani; Hamoud Ali Algarani; Meshal Aber Alonazi; Kumar Chandan Sirivastava; Rakhi Issrani (BMC, 2022)
Abstract Background Adequate knowledge of root canal morphology and possible variations is essential to achieve perfect root canal treatment and overcome treatment failure. Appropriate knowledge on root and canal morphology, communication, and documentation amongst dentists will be challenging from a diagnostic and successful treatment point of view. Methods A total of 3420 samples were included in this study from 285 cone-beam computed tomography images of the Saudi residents, including 171 males and 114 females aged 15 to 68 years from retrospective data dated from January 2018 to April 2021. The images were examined in sagittal, axial and coronal views using a 3D version software 1.0.10.6388. The number of canal and canal morphology was recorded using Vertucci and the new classification system. The SPSS 26 was used to conduct the statistical analysis as descriptive statistics such as mean; standard deviation and frequency were calculated. The Chi-square test analysed the data with the significance level set at 0.05. Results A total of 285 subjects participated in the study. Majority of the participants were Saudi nationals (80.7%), followed by Indian (7.4%), Pakistani (4.2%) and other nationalities. According to Vertucci and the new classification system, Type I and 1TN1 were the most common types, followed by Type III and Type IV, and then 1TN1-2-1 and 1TN1-2 in mandibular anteriors. The prevalence of canal variations in mandibular canine was higher in females than in males (P = 0.002). Maxillary laterals and mandibular anteriors showed the significant difference in the prevalence of root canal variation in relation to the ethnicity (P = 0.001) and age of the patients. Younger patients showed more variations than the older patients (P = 0.012, P = 0.023, P = 0.001, P = 0.001) in terms of maxillary laterals, mandibular central, laterals and canines, respectively. Conclusion Mandibular permanent anteriors showed a wide range of canal variations and canal complexity. Males and females did not demonstrate a wide range of variation in the root canal morphology except for the canines in relation to the gender of the patients.